School Leadership in Improving the Quality of Education at Integrated Islamic SMP Nurul Fadillah Deli Serdang - Adlin Damainik; Ika Muntazah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine the principal's leadership in improving the quality of SMP IT Nurul Fadhillah, the constraints of the principal's leadership in improving the quality of schools at SMP IT Nurul Fadhilah, and the principal's efforts to improve the quality of schools at SMP IT Nurul Fadhilah. The method used in this research is qualitative research with a descriptive approach and the techniques used are observation, interviews and documentation. The subjects of this study were the principal and teachers. Data analysis techniques use data reduction, data presentation and conclusions. Ensuring the validity of research data uses credibility, transfibility, dependability and conformability. The results of this research are the principal's leadership in improving the quality of education by caring for subordinates, assertiveness, democracy, and supervision. The obstacles faced by school principals in improving the quality of schools are the lack of educational facilities and infrastructure. As for the efforts made by the principal in improving the quality of education, namely developing teacher competence, meeting the needs of school stakeholders and getting used to working together in overcoming problems.